2020
DOI: 10.1175/bams-d-19-0265.1
|View full text |Cite
|
Sign up to set email alerts
|

Weather Patterns Associated with Pain in Chronic-Pain Sufferers

Abstract: The belief that weather influences people’s health has been prevalent for millennia. Recent studies on the relationship between weather and pain for those who suffer from chronic pain remain indeterminate, with some studies finding strong effects and others finding no effects; most studies face limitations to their study design or dataset size. To address these limitations, a U.K.-wide smartphone study Cloudy with a Chance of Pain was conducted over 15 months with 10,584 citizen scientists who suffer from chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Earlier research has found that chronic pain sufferers experience more pain when meteorological variables fall of normal ranges, ie, when barometric pressure is lower and precipitation, relative humidity, and wind speed are higher than normal. 10,32 Such observations are in line with our result of local minima in CPT coinciding with below-normal barometric pressure and above-normal relative humidity. Earlier research has suggested that chronic pain sufferers have a lower pain tolerance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Earlier research has found that chronic pain sufferers experience more pain when meteorological variables fall of normal ranges, ie, when barometric pressure is lower and precipitation, relative humidity, and wind speed are higher than normal. 10,32 Such observations are in line with our result of local minima in CPT coinciding with below-normal barometric pressure and above-normal relative humidity. Earlier research has suggested that chronic pain sufferers have a lower pain tolerance.…”
Section: Discussionsupporting
confidence: 89%
“… 41 In a study of weather patterns and pain, chronic pain sufferers experienced the most pain on days characterized by below-normal barometric pressure, higher precipitation, above-normal relative humidity, and stronger winds. 32 However, other studies have shown conflicting results; many authors have concluded that the effect of weather on pain is either nonexistent or very small. 3 , 42 These conflicting results could be due to differing methodologies, the complexity underlying pain, and how we experience weather.…”
Section: Introductionmentioning
confidence: 99%
“…Participants were required to provide electronic consent for study inclusion. Further details are available elsewhere [ 2 , 3 ].…”
Section: Methodsmentioning
confidence: 99%
“…To determine what daily average weather conditions participants were exposed to, the app recorded participants’ geolocation, which we could link to weather reports from local weather stations. The analysis of the weather and pain association and the details of data collection are described elsewhere [ 2 , 3 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation